Underinvestment and capital misallocation under sovereign risk - Carlos Esquivel (Rutgers University, Department of Economics, 2024)
Capital and its sectoral allocation affect default incentives. Under general assumptions, default risk is decreasing in the total stock of capital and increasing in the share of capital allocated to non-tradable production. This implies that when competitive households make all investment decisions capital has two externalities: a capital-stock externality and a portfolio externality. These hamper the ability of a benevolent government to make optimal borrowing and default decisions and are exacerbated during periods of distress. Competitive equilibria feature underinvestment, larger non-traded sectors, more default, and lower debt and consumption than a centralized planner's allocation.
Keywords: F34; F41; H63; 330; Sovereign default; Underinvestment; Investment externalities